Level of awareness about Shehu Usmanu Danfodiyo among some private school students in Gwadabawa, Sokoto, Nigeria: A cross-sectional survey - Tambari Abbas Bashar (Interdisciplinary Social Studies, 2025)
This study aims to assess the level of awareness, interest, and practice about Shehu Usmanu Danfodiyo among some private secondary school students in Gwadabawa, Sokoto State, Nigeria, using a cross-sectional survey. The study utilizes a mixed-methods approach, utilizing both quantitative surveys and qualitative interviews, to provide comprehensive insights into the effectiveness of such educational strategies. The findings revealed that, there is a poor level of knowledge about sokoto Caliphate, which might be due to poor implementation of curriculum or poor attention of students to the Islamic studies or related religious subjects been taught at schools. However, the study also shows that, with proper instruction and teaching, the students can develop a significant degree of awareness about Sheheshu and Sokota Calipahate. Therefore, this work serves as a foundational step for further studies aimed at improving cultural and historical education in the region, ultimately fostering a greater appreciation of local heritage among students.